2015
DOI: 10.1016/j.cmi.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Decline in antibiotic resistance and changes in the serotype distribution of Streptococcus pneumoniae isolates from children with acute otitis media; a 2001–2011 survey by the French Pneumococcal Network

Abstract: Streptococcus pneumoniae is an important cause of acute otitis media (AOM). The aim of this study was to evaluate trends in antibiotic resistance and circulating serotypes of pneumococci isolated from middle ear fluid of French children with AOM during the period 2001-2011, before and after the introduction of the PCV-7 (2003) and PCV-13 (2010) vaccines. Between 2001 and 2011 the French pneumococcal surveillance network analysed the antibiotic susceptibility of 6683 S. pneumoniae isolated from children with AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 19 publications
4
26
0
4
Order By: Relevance
“…Another recent French study evaluated the trends in antibiotic resistance and serotype distribution of pneumococci isolated from MEF in children with AOM from 2001 to 2011. 36 The authors reported a marked reduction in infection with vaccine serotypes after PCV7 implementation, from 63.0% in 2001 to 13.2% in 2011, with increased incidence of infection with the additional 6 serotypes included in PCV13 during the same period, with a particularly high proportion of 19A isolates. 36 After PCV13 implementation, H. influenzae was the most frequent otopathogen isolated and accounted for 75.9% of positive MEF samples.…”
Section: Impact Of Pcvs On Aom Treatment Failurementioning
confidence: 99%
See 3 more Smart Citations
“…Another recent French study evaluated the trends in antibiotic resistance and serotype distribution of pneumococci isolated from MEF in children with AOM from 2001 to 2011. 36 The authors reported a marked reduction in infection with vaccine serotypes after PCV7 implementation, from 63.0% in 2001 to 13.2% in 2011, with increased incidence of infection with the additional 6 serotypes included in PCV13 during the same period, with a particularly high proportion of 19A isolates. 36 After PCV13 implementation, H. influenzae was the most frequent otopathogen isolated and accounted for 75.9% of positive MEF samples.…”
Section: Impact Of Pcvs On Aom Treatment Failurementioning
confidence: 99%
“…22,26,36,39,40 Indeed, we previously demonstrated the strong impact of the PCV7 implementation, combined with reduced antibiotic use, on the carriage of penicillin non-susceptible pneumococci in children with AOM. 22 After PCV13 implementation, because selective pressure continues to occur with excessive antibiotic consumption in France, some non-vaccine serotypes are frequently resistant.…”
Section: Impact Of Pcvs On Antibiotic Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Notably, before the 1990s, most S. pneumoniae strains demonstrated universal sensitivity to penicillin (12). Today, however, penicillin resistance varies from 5-60% in various parts of the world (13,14). Of particular concern is the increase in multidrugresistant S. pneumoniae strains demonstrating resistance to three or more drug classes (15)(16)(17)(18), which creates substantial concerns about both the efficacy of current antibiotic regimens and the continual development of resistance.…”
mentioning
confidence: 99%